Gabon : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2002)
This 2001 Article IV Consultation highlights that the fiscal and structural reform efforts in Gabon continued during 2001 under the government's program supported by an 18-month Stand-by Arrangement, approved on October 23, 2000. Non-oil economic activity in Gabon rose by 4 percent in 2001, following a severe contraction in 1999 and a moderate recovery in 2000. Private investment picked up as confidence strengthened further, helped by substantial repayments of government domestic debt. Services, agriculture, and wood processing were the main sectors contributing to growth.